2008
DOI: 10.1080/08037050802218417
|View full text |Cite
|
Sign up to set email alerts
|

Association of aortic pressures with fasting plasma glucose in patients with and without impaired fasting glucose

Abstract: Ascending aorta PP and FPPs are significantly associated with the presence of IFG. These findings suggest that IFG is associated with endothelial dysfunction and so aortic stiffness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…45 In addition, our results are consistent with prior invasive studies that demonstrated that central pulse pressure is different between those with normal fasting glucose and those with impaired fasting glucose. 46 Second, a selection bias may be present in our study. The MESA study specifically recruited individuals without cardiovascular disease, and as such, our participants may have more resistance or fewer risk factors than the general population to cardiovascular disease.…”
Section: Discussionmentioning
confidence: 92%
“…45 In addition, our results are consistent with prior invasive studies that demonstrated that central pulse pressure is different between those with normal fasting glucose and those with impaired fasting glucose. 46 Second, a selection bias may be present in our study. The MESA study specifically recruited individuals without cardiovascular disease, and as such, our participants may have more resistance or fewer risk factors than the general population to cardiovascular disease.…”
Section: Discussionmentioning
confidence: 92%
“…Consistent with previous research, in our study fasting plasma glucose was positively and independently associated with the future pulse pressure. Cay et al [42] showed that subjects with impaired fasting glucose had significantly greater aortic pulse pressure compared with those with normal fasting glucose. In addition, other work has demonstrated a positive association between fasting plasma glucose levels with arterial stiffness in non-diabetic subjects [43, 44].…”
Section: Discussionmentioning
confidence: 99%
“…Arterial stiffness in patients with abnormal glucose metabolism Increased arterial stiffness has been established as a risk factor for coronary artery disease and coronary artery plaque burden [21][22][23]. Arterial stiffness in patients with diabetes mellitus (DM) or impaired glucose metabolism has also been studied extensively using various tools such as augmentation index, carotid-femoral transit time, or arterial compliance [8,[24][25][26]. Central and peripheral arterial stiffness both have shown an association with impaired glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%